A Systematic Literature Review on Entrepreneurial Intuition Among Students: Trends and Future Directions - Agus Wibowo; Mohammad Sofwan Effendi; Bagus Shandy Narmaditya (Economics Education Department Universitas Negeri Semarang, 2024)
Entrepreneurship has been an important predictor of resolving the problem of unemployment in Indonesia and other countries through the creation of new jobs. Academics, scholars, and policy researchers especially promote entrepreneurial strategies because of their important role in expanding innovation, enhancing economic growth, and supporting economic development. The primary purpose of this study is to systematically identify and evaluate entrepreneurial intuition research. This study involved data from the Scopus database from 2004 to 2024 using preferred reporting items for systematic reviews and meta-analyses (PRISMA) protocol. For visualization, this study involved VOSviewer software to determine the linkage of variables. The findings indicate that entrepreneurial intuition is often linked with several factors: sustainability, technology usage, and cognitive process. The findings also conclude that there is a robust relationship between entrepreneurial intuition and entrepreneurial intention. This paper also highlights the trend of entrepreneurial ideas for student education and the key role of entrepreneurial learning in enhancing entrepreneurial intuition. The findings of this paper are to allocate avenues for future research on the theme of entrepreneurial intuition.